Revisiting Campylobacter jejuni Virulence and Fitness Factors: Role in Sensing, Adapting, and Competing - Elmi, Abdi; Nasher, Fauzy; Dorrell, Nick; Wren, Brendan; Gundogdu, Ozan (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter jejuni is the leading cause of bacterial foodborne gastroenteritis world wide and represents a major public health concern. Over the past two decades, significant progress in functional genomics, proteomics, enzymatic-based virulence profiling (EBVP), and the cellular biology of C. jejuni have improved our basic understanding of this important pathogen. We review key advances in our understanding of the multitude of emerging virulence factors that influence the outcome of C. jejuni–mediated infections. We highlight, the spatial and temporal dynamics of factors that promote C. jejuni to sense, adapt and survive in multiple hosts. Finally, we propose cohesive research directions to obtain a comprehensive understanding of C. jejuni virulence mechanisms.